2013
DOI: 10.14207/ejsd.2013.v2n3p35
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Comparative Advantage of Mauritius

Abstract: The authors investigated whether Mauritius has comparative advantage in the products it exports in intra-SADC, intra-COMESA and global markets. There is a need for Mauritius to improve its competitiveness through a combination of both regional and national strategies via increasing investment in infrastructural development, promotion of intra-regional trade and integration, improving capacity building, liberalization of the labour market and facilitating the access to banking resources. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…Where the index value is greater than 1, the country has a revealed comparative advantage in the relevant good; in cases where the index value is less than 1, it is concluded that the country does not have a comparative advantage in the relevant product (Mushanyuri & Mzumara, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Where the index value is greater than 1, the country has a revealed comparative advantage in the relevant good; in cases where the index value is less than 1, it is concluded that the country does not have a comparative advantage in the relevant product (Mushanyuri & Mzumara, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Daya saing komoditas suatu negara bisa diukur dengan menghitung keunggulan komparatif. Metode perhitungan keunggulan komparatif yang kerap digunakan dalam penelitian sebelumnya adalah Revealed Comparative Advantage (RCA) (Bano & Scrimgeour, 2012;Ermawati & Saptia, 2013;Herciu, 2013;Kaunang, 2013;Mushanyuri & Mzumara, 2013;Sarwono & Pratama, 2014;Suntharalingam et al, 2011).…”
Section: Indeks Keunggulan Komparatifunclassified
“…The PDM describes that the Government of Indonesia (GoI) should improve the infrastructure in North Sulawesi, subsidize the fertilizer for coconut plant, and develop the technology of the coconut oil industry. Mushanyuri & Mzumara (2013) Zuhdi & Suharno (2015) analyzes the export competitiveness of Indonesian and Vietnamese coffee in the ASEAN 5 market by applying the RCA and the EPD. The RCA indices indicate that Vietnam has better export competitiveness than Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%